Mapping the learning trajectories of physical sciences teachers' topic specific knowledge for teaching chemical bonding - Toerien, René (School of Education, 2017)
Education in South Africa is a national concern and the training and professional development of teachers, especially in science and mathematics, has consequently been prioritised by the National Government. More than 60 percent of the teachers in South Africa are older than 40 years of age, which means that within the next 10-15 years many experienced teachers will exit the system, leaving a younger and less experienced cohort of teachers behind. This study aims to make explicit the learning trajectories of physical sciences teachers, specifically with respect to their knowledge for teaching chemical bonding, in order to support other teachers and thereby accelerating the route to expertise. Learning can be viewed as change, and change has a trajectory. Mapping the learning trajectories, and the significant events that influenced teachers' learning over time, can give insight into how the change had taken place. This study used a mixed methods approach within the pragmatic research paradigm to map learning trajectories for a group of 60 South African physical sciences teachers. Pedagogical content knowledge (PCK), the unique knowledge held by teachers, was used for the theoretical framing of the study. An adapted version of the Model of Teacher Professional Knowledge and Skill, including PCK, was used as an analytical framework. A measuring instrument for topic specific knowledge for teaching chemical bonding was designed and validated using the Rasch measurement model. Quantitative and qualitative analysis of the teachers' responses to the instrument and a grounded analysis of story-line interview data from ten purposively selected teachers were used to identify the factors that played a role in the development of the teachers' knowledge. A further qualitative analysis of PCK episodes from the interview data revealed how the above factors influenced the teachers' knowledge. Findings revealed that teaching the same content multiple times and at multiple grade levels, embracing changes in the curriculum as opportunities for learning, and further studies at tertiary level, especially completing post-graduate studies in education, all played a role in the teachers' perceived shifts in their topic specific knowledge for teaching (TSKFT). Three learning trajectories were identified for the teachers in this study: teachers shifted towards deeper conceptual understanding of the content and used more sophisticated explanatory frameworks; teachers shifted towards more integrated topic specific knowledge for teaching; and teachers shifted from being text book bound and teacher-focussed towards becoming more student-focussed in their approach to teaching. The findings from this study provide guidelines for professional development programmes in terms of differentiated support to teachers according to their career stages and the inclusion of content specific training programmes which makes teaching for conceptual progression explicit. A further recommendation includes encouraging teachers to embark on post-graduate studies in education as this played a pivotal role in shifting teachers' topic specific knowledge for teaching chemical bonding.